MNG-2 Meningioma with aseptic meningitis. (6th December 2021) - Nakajima, Hideki; Tsuchiya, Takuro; Shimizu, Shigetoshi
Abstract: The patient, a woman in her seventies, visited the Department of Neurology at our hospital one month ago with transient right hemiparesis, and was referred to our department because a CT scan showed a 4cm extramedullary lesion in the left convexity. She was judged to have symptomatic epilepsy associated with the lesion and was started on antiepileptic drugs. The lesion showed low signal on T1WI, equal signal on T2WI, and homogeneous contrast on Gd contrast T1WI, suggesting a meningioma, but the surrounding left frontal lobe subarachnoid space was also contrasted, suggesting the possibility of seeding or other diseases. After that, the contrast area of the subarachnoid space increased in a short period of time, and the control of epileptic seizures was poor. Preoperative spinal fluid examination showed an elevated cell count and findings of aseptic meningitis. A left parietal craniotomy was performed to remove the extramedullary tumor as much as possible. The subarachnoid space of the left frontal lobe adjacent to the tumor was covered with extensive pale yellow apparently abscess-like tissue. The pathological diagnosis of the extramedullary tumor was angiomatous meningioma (WHO Grade 1), and the pale yellow tissue that filled the subarachnoid space was necrotic tissue containing neutrophils and no tumor component. IgG4 was positive in about 10% of the tumor. The postoperative course of the patient was good, the contrast area of the left frontal lobe subarachnoid space was reduced on MRI, aseptic meningitis was improved, and she was discharged home with no neurological deficits. The patient has been under outpatient observation for 2 years without recurrence of aseptic meningitis or appearance of contrast-enhancing lesions in the subarachnoid space. This case is thought to be a possible IgG4-related disease, and we report it with a discussion of the literature.